Role of LAVi/A’ and E/’ as A Predictor of Major Adverse Cardiac Event on Patient with Acute Myocardial Infraction with ST Segment Elevation Undergo Through Percutaneous Coronary Intervention - Aditya Reza Pratama; Budi Satrijo; Anna Fuji Rahimah; Djanggan Sargowo; Cholid Tri Tjahjono; Muhammad Rizki Rizki Fadlan (Universitas Brawijaya, 2021)
Introduction:STEMI is still a major health problem in industrialized and developing countries. The risk of adverse cardiovascular events remains substansial and may vary significantly across of STEMI patients. Echocardiography is recommended tool for diagnosis and predict outcomes. Increased LA volume index (LAVI) has been shown to be a powerfull predictor of mortality after AMI. The ratio of the left atrial volume index (LAVI) and late diastolic mitral annular velocity (A’) is additional benefits in the assessment od advance diastolic dysfunction in ACS for predicting outcome.Methods:This study retrospective cohort was conducted in patient admitted to Saiful Anawar General Hospital with STEMI who undergo PCI from 2019-2020. All patient underwent echocardiography measurement within 24-48 hours and we follow-up patient for 6 months until 12 months. Echocardiography measurement that we conducted were LVEF, E/A, E/e’, LAVI/A’ and LV diastolic function were measured according to ASE guidelines. All of the patients were given standard medical therapy. Patients who did not adhere to medication were excluded. The study endpoints were hospitalisation and mortality because of cardiac problem. Result:We collected the data from 169 STEMI patients. However, about 39 STEMI patients were excluded because of incomplete data, lost follow-up, become atrial fibrillation, refused participation and death. Finally, a total of 130 patients were involved in the analysis process. The patients mean age was 61.48 ± 7 years, and 78% of them were male. The receiver operating characteristics curve indicated that LAVI/A’ ≥ 4.0 predicted these events (AUC 0.892, 95% CI 0.819-0.965) and E/e’ ≥ was 13.4 (AUC 0.874, 95% CI; 0.806-0.942). The MACE incident in 6 months with LAVI/A’ ≥ 4.0 was 40%, E/e’ ≥ 13.4 was 20% and LAVI/A’ ≥ 4.0 + E/e’ ≥ 13.4 was higher 60%. The incidence MACE incident was LAVI/A’ > 4.0 sensitivity 92% and specifity 88% (CI 95%), E/e’ > 13.4 sensitivity 80% and specifity 74% (CI 95%), LAVI/A’ > 4.0 + E/e’ > 13.4 sensitivity 92% and specifity 88% (CI 95%). Conlussion:The LAVI/A’ ratio is available as echo index which reflects LV chronic diastolic function in patient with STEMI. It can predict MACE, particularly in those with STEMI undergo PCI. Combined LAVI/A’ > 4.0 and E/e’ >13,4 ratio suggests MACE better than LAVI/A’ > 4.0 and E/e’ >13,4 alone.Keywords: ST-elevation Myocardial Infarction, Echocardiography, LAVI/A’, E/e’, Percutaneous Coronary Intervention